2013
DOI: 10.1021/es304580r
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors Controlling the Transport of Silver Nanoparticles in Porous Media

Abstract: The current study investigated the mobility of four silver nanoparticles (AgNPs) stabilized using different capping agents and represent the common stabilization mechanisms as well as surface charging scenarios in reactive and nonreactive porous media. The AgNPs were (1) uncoated H2-AgNPs (electrostatically stabilized) and (2) citrate coated AgNPs (Citrate-AgNPs) (electrostatically stabilized), (3) polyvinylpyrrolidone coated AgNPs (PVP-AgNPs) (sterically stabilized), and (4) branched polyethyleneimine coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 36 publications
2
56
1
Order By: Relevance
“…For example, the retention of NPs may occur even under unfavorable conditions for attachment due to local surface charge heterogeneities (Lin et al, 2011), aggregation (Bradford et al, 2006), and straining in small pores and at locations of high surface roughness (Kasel et al, 2013a). Additionally, an increase in the NPs transport due to stabilizing agents causing short-range repulsive forces (El Badawy et al, 2013), retarded and asymmetric BTCs, and uniform, non-monotonic, and hyperexponential retention profiles (RPs) (Liang et al, 2013a) are examples of violations of the filtration theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the retention of NPs may occur even under unfavorable conditions for attachment due to local surface charge heterogeneities (Lin et al, 2011), aggregation (Bradford et al, 2006), and straining in small pores and at locations of high surface roughness (Kasel et al, 2013a). Additionally, an increase in the NPs transport due to stabilizing agents causing short-range repulsive forces (El Badawy et al, 2013), retarded and asymmetric BTCs, and uniform, non-monotonic, and hyperexponential retention profiles (RPs) (Liang et al, 2013a) are examples of violations of the filtration theory.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers have studied the transport of AgNPs in highly idealized systems consisting of repacked, homogeneous, coarse-textured porous media (e.g., glass beads, quartz sands) under water-saturated or unsaturated conditions (e.g., El Badawy et al, 2013;Fang et al, 2013;Liang et al, 2013b). While these studies have provided valuable insights into the mechanisms controlling the transport of AgNPs, they do not exactly resemble natural soil conditions.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, the presence of surfactants, natural organic matter and bacteria can modify the interactions between NP and porous media, resulting in a reduction of NP retention (Chen et al, 2012;Chowdhury et al, 2012;Godinez and Darnault, 2011;Godinez et al, 2013;Wang et al, 2012). For more complex porous media, columns of soil (Cornelis et al, 2013;Fang et al, 2009;Liang et al, 2013a) and sand with reactive coatings (El Badawy et al, 2013;Wang et al, 2012) have been used. It was found that TiO 2 NPs are more retained in soils with a high clay content and strong salinity.…”
Section: Introductionmentioning
confidence: 99%
“…One way to evaluate retention mechanism effects is to apply filtration theory (El Badawy et al, 2013;Li et al, 2011;Petosa et al, 2012), which takes into account physicochemical conditions and describes the frequency of collisions between nanoparticles and collector grains. The parameters of filtration theory offer a simple description of deposition dynamics but can be quite imprecise in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…There are many situations where small objects subject to Brownian motion in a fluid are introduced to the constriction of microscopic channels, for example, filtration of colloidal particles through porous media [1][2][3], translocation of DNA molecules through nanopore sequencers [4][5][6][7][8][9][10][11][12][13][14][15][16][17], and lab-on-achip (LOC) devices where analytes are introduced to various domains of nano-and microchannels for analysis [18][19][20][21][22][23][24][25]. It is now well known that the translocation phenomena of polymer molecules through nanopores with a diameter comparable to the monomer size have stochastic nature [5,6].…”
Section: Introductionmentioning
confidence: 99%